PERANAN DAN KEDUDUKAN HUKUM BADAN USAHA MILIK NEGARA DALAM KEUANGAN NEGARA - Evi Oktarina; Liza Deshaini (Justici, 2021)
ABSTRACT The state controls the natural resources but the State does not try to monopolize the natural resources. This is because it will result in commercial government. In order for the government to run well, the State established a State-Owned Enterprise (BUMN) to exploit the natural wealth for the welfare of the people. The making of this research uses a normative research methodology, namely through the search and analysis of secondary legal materials. The problems that arise are the role of SOEs in the rule of law and the legal position of SOEs in state finance. SOEs in the rule of law play a role in carrying out activities in the economic and trading where the Government can own all or part of the shares or capital in a company. While the legal status of SOEs in state finance is the inclusion of state assets in SOE capital as a result of the separation of state assets as determined in Act Number 19 of 2003 concerning SOEs.